Business Models and Digital Technology Platforms : Implementation and Complexities for Digital Business. - Bartczak, Krzysztof. (Routledge Studies in Innovation, Organizations and Technology Series, 2024)
This book examines the influence exerted by digital technology platforms on changes to business models. The author identifies critical factors for the successful implementation and usage of such platforms, including barriers which may be related.